An interpersonal approach to classroom management : strategies for improving student engagement - Davis, Heather A.; Miller, Lauren M.; Summers, Jessica J. (Thousand Oaks, Calif. : Corwin Press : Division 15 (Educational Psychology) of the APA, 2012)
Bridges the gap between educational psychology and peer and student-teacher management, with focus on student engagement, classroom relationships, and teacher self-regulation.
Includes bibliographical references (p. 203-224) and index.
Professional
Professional
Keywords: Classroom management; Classroom management; Educational psychology; Educational psychology; Teacher-student relationship; Teacher-student relationships